Antiviral activity of alginate-oleic acid based coatings incorporating green tea extract on strawberries and raspberries. (February 2019) - Falcó, Irene; Flores-Meraz, Patricia L.; Randazzo, Walter; Sánchez, Gloria; López-Rubio, Amparo; Fabra, María José
Abstract: Foodborne illnesses caused by the consumption of berries contaminated with human enteric viruses, namely human noroviruses (NoVs) and the hepatitis A virus (HAV), remain a significant food safety concern. The objective of this research was to investigate a food-grade edible coating composed of alginate/oleic and containing green tea extract (GTE) as an antiviral agent for the preservation of fresh strawberries and raspberries. Berries were stored at ambient (25 °C) temperature and refrigerated (10 °C) conditions. Initially, the effect of the pH of the film-forming dispersions (FFD) on their antioxidant and antiviral activity was analysed. Then, the physicochemical properties of edible alginate-oleic acid coatings containing GTE were studied, and finally, their antiviral efficacy when applied onto strawberries and raspberries at 10 and 25 °C was evaluated. The results showed that the antioxidant properties of the films were not pH-dependent, but the antiviral activity was higher at a pH 5.5. The infectivity of the murine norovirus (MNV), a human norovirus surrogate, and HAV in fresh strawberries after the coating treatments was reduced by approximately 1.5–2 log during the 4-days storage period at 10 °C as compared to the controls and a complete inactivation of both viruses was observed after overnight storage at 25 °C. However, the efficacy of the GTE-coatings was slightly reduced on the raspberries, probably due to the difference in the amount of coating that adhered to their surface (4.64 ± 0.23 g and 1.54 ± 0.15 g⋅cm −2 for strawberries or raspberries, respectively). Therefore, this paper reports, for the first time, the potential of antiviral edible coatings to improve the safety of berries against foodborne pathogens. Graphical abstract: Image 1 Highlights: Antiviral food-grade coatings containing green tea extract (GTE) were prepared. The antioxidant properties of the films were not pH-dependent. The antiviral activity against MNV and HAV was higher at pH 5.5. Antiviral coatings were effective at ambient and refrigerated conditions. The antiviral efficacy of GTE-coatings was greater in strawberries than in raspberries.